Seroprevalence and associated risk factors of human Brucella infection in selected provinces in Sri Lanka - Karunanayake, L.; Karunanayake, P.; Rathnayaka, C.S.; Senarath, U.; Ranbanda, J.M.; Kothalawala, M. (Sri Lanka Medical Association, 2019)
Brucellosis is a systemic zoonotic bacterial infection. We studied the seroprevalence and risk factors for human Brucella infection in 1,294 healthy people from 4 provinces: Central, North-Western, North-Central and Western Provinces. Farmers in contact with farm-animals, veterinary staff, abattoir workers, and non-contact urban-dwellers were tested against B. abortus and B. melitensis antigens by SAT. Seroprevalence was 8.4% of the study population. Farm-animal owners and working full-time with livestock have a significantly higher risk of acquiring Brucella infection. Enhanced laboratory support and surveillance is necessary to control brucellosis in Sri Lanka. This is the first report on human Brucella infection.
Keywords: Brucellosis; human Brucella infection; Prevalence; Risk factors; Sri Lanka